2005
DOI: 10.1086/444371
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Spectra of Polycyclic Aromatic Hydrocarbon Emission in Herbig Ae/Be Stars

Abstract: We present spectra of four Herbig AeBe stars obtained with the Infrared Spectrograph (IRS) 1 on the Spitzer Space Telescope. All four of the sources show strong emission from polycyclic aromatic hydrocarbons (PAHs), with the 6.2 µm emission feature shifted to 6.3 µm and the strongest C−C skeletal-mode feature occuring at 7.9 µm instead of at 7.7 µm as is often seen. Remarkably, none of the four stars have silicate emission. The strength of the 7.9 µm feature varies with respect to the 11.3 µm feature among the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 44 publications
12
109
1
Order By: Relevance
“…In observed spectra of different lines of sight of the interstellar medium, sp 3 aliphatic hydrocarbons can be detected at 3.4, 6.85 and 7.25 μm, whereas sp 2 aromatic hydrocarbons can be observed at 3.28 μm and 6.2 μm of =CH and C=C stretching modes, respectively, toward the galactic center (Chiar et al 2000). For the 6.2 μm band, the astronomical observations (Sloan et al 2005(Sloan et al , 2007 have shown that there are three band positions corresponding to A, B and C-class PAHs. In addition to the unidentified bands in these observations, several out-of-plane PAH-bands such as 11.3, 12.0, and 12.7 μm have been observed.…”
Section: Astronomical Implicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…In observed spectra of different lines of sight of the interstellar medium, sp 3 aliphatic hydrocarbons can be detected at 3.4, 6.85 and 7.25 μm, whereas sp 2 aromatic hydrocarbons can be observed at 3.28 μm and 6.2 μm of =CH and C=C stretching modes, respectively, toward the galactic center (Chiar et al 2000). For the 6.2 μm band, the astronomical observations (Sloan et al 2005(Sloan et al , 2007 have shown that there are three band positions corresponding to A, B and C-class PAHs. In addition to the unidentified bands in these observations, several out-of-plane PAH-bands such as 11.3, 12.0, and 12.7 μm have been observed.…”
Section: Astronomical Implicationsmentioning
confidence: 84%
“…This means that there is a transformation from aliphatic to aromatic structures resulting in larger aromatic units. In the range of 10-15 μm, the spectra have revealed emission features at 11.2, 12.7, 13.5, and 14.2 μm (Hony et al 2001;Sloan et al 2005) in different astrophysical environments. They are caused by CH out-of-plane bending modes of PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…Jura et al (2006) also report on the detection of class-C PAH features in a circumstellar disc around the oxygen-rich K-giant HD 233517. Two young objects, the T Tauri star SU Aur (Furlan et al 2006) and the Herbig Ae/Be source HD 135344 (Sloan et al 2005), also show PAH spectra of class C, although in HD 135344 the PAH features seem to be somewhat more in between B and C. This source is also slightly hotter than other class C sources. A comparison of the PAH features in all these sources is given by Sloan et al (2007).…”
Section: Pah Featuresmentioning
confidence: 91%
“…In contrast, the spectra reveal no evidence for emission from polycyclic aromatic hydrocarbons. These (carbon-rich) molecular compounds are found in the infrared spectra of the interstellar medium (Draine, 2003), some circumstellar environments (Sloan et al, 2005), and in comets (Bockelée-Morvan et al, 1995), with strong features near 6, 8, and 11 µm. Hence, the circumstellar dust at white dwarfs appears relatively carbon-deficient and rocky (Jura et al, 2009a), and likely similar to the material of the inner Solar System.…”
Section: Infrared Spectra Of Disksmentioning
confidence: 98%